2023
DOI: 10.3390/agriculture13122248
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Environmental Attitudes and Risk for Adoption with Respect to Farmers’ Participation in the Agri-Environmental Practices

Jelena Vapa Tankosić,
Svetlana Ignjatijević,
Nemanja Lekić
et al.

Abstract: This research represents an attempt to systematically introduce the concepts of sustainable agriculture that shall address environmental attitudes and the risks for adoption related to agri-environmental practices. The substantial risks posed by climate change, loss of biodiversity, and other forms of pollution within the 21st century regarding global eco-systems, food production, and human health have emphasized the need to investigate this phenomenon. The agri-environmental practices are aimed at mitigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…For example, agriculture certification, which allows farmers to sell their products at higher prices in the premium markets, enhanced compliance with environmental legislation [23]. In Serbia, farmers were willing to adopt agri-environmental measures in return for long-term economic benefits [24]. Neves et al [25] found that penalizing polluting activities in the form of taxes and reinforcing clean activities by subsidies and financial benefits were effective in reducing CO 2 emissions in European Union countries.…”
Section: Compliance With the Environmental Lawsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, agriculture certification, which allows farmers to sell their products at higher prices in the premium markets, enhanced compliance with environmental legislation [23]. In Serbia, farmers were willing to adopt agri-environmental measures in return for long-term economic benefits [24]. Neves et al [25] found that penalizing polluting activities in the form of taxes and reinforcing clean activities by subsidies and financial benefits were effective in reducing CO 2 emissions in European Union countries.…”
Section: Compliance With the Environmental Lawsmentioning
confidence: 99%
“…Onyando et al [34] found that low awareness may hinder the safe use of pesticides by farmers. Vapa Tankosić et al [24], found that farmers were more willing to accept the AEM if they felt that preservation of the environment was essential for protecting the resources for future generations. Also, the adoption of AEM by farmers can be enhanced by increasing training and environmental education that demonstrate the environmental benefits.…”
Section: Compliance With the Environmental Lawsmentioning
confidence: 99%
See 3 more Smart Citations